Inovasi Media Pembelajaran dalam Meningkatkan Skill Abad 21: Penggunaan Media Magnetic Alphabet dalam Meningkatkan Kemampuan Membaca Permulaan Anak Autism Spectrum Disorder (ASD) - Anggi Setiawati; Luthfatun Nisa’; Danang Prastyo; Nurahmad (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
Children with Autism Spectrum Disorder (ASD) often face difficulties in early reading due to challenges in communication and symbol recognition. Conventional learning methods are generally ineffective for them, as they tend to learn better through visual, auditory, and kinesthetic approaches. Therefore, an innovative, interactive, and engaging learning medium is needed. One such tool is the Magnetic Alphabet Educational Game (APE), which not only aids in letter recognition and word construction but also supports the development of 21st-century skills such as communication and critical thinking. This study employs a qualitative case study approach at TK Muslimat NU VI Pamekasan to examine the effectiveness of the Magnetic Alphabet APE in enhancing the early reading skills of children with ASD aged 5–6 years. The findings show that this media significantly improves focus, letter recognition, and word-building abilities. Supporting factors include visual appeal and teacher involvement, although challenges such as limited tools and varying levels of understanding remain. This media is recommended for use in inclusive schools and at home as an effective literacy strategy for children with special needs.